Do self‐efficacy and depression predict oral impacts on daily performances across time? A 2‐yr follow‐up of students in Tanzania. (18th April 2016) - Åstrøm, Anne N.; Lie, Stein A.; Mbawalla, Hawa
Abstract : This study aimed to assess the longitudinal validity of the oral impacts on daily performance (OIDP) and to identify psychosocial determinants, in terms of self‐efficacy and depressive symptoms, of the OIDP across time. Following conceptual frameworks of oral health, it was hypothesized that sociodemographic, clinical, and psychosocial factors predict oral impacts across time at both population‐ averaged and person‐specific levels. Whether the effects of sociodemographic and clinical factors were accounted for, totally or in part, by psychosocial factors were also investigated. Self administered questionnaires and oral clinical examinations at baseline (2009) and follow‐up (2011) were completed by 1, 714 and 727 secondary school students, respectively. Generalized equalized equations and a random intercept model were used to account for the dependency in repeated observations. Mean OIDP change scores were negative (worsened) among those who reported worsened self‐reported oral health. Psychosocial, clinical, and sociodemographic factors were independently associated with oral impacts at the population‐averaged and person‐specific levels. Mediation of sociodemographic and clinical variables according to psychosocial variables was not observed. Satisfactory longitudinal evaluative properties of the OIDP, and independent effects of psychosocial factors on oral impacts across time, were confirmed among secondary school students in Tanzania.